Economic public order and the guarantee of free competition in the market - Zina, Haddad (The International tax journal, 2026)
Various economic and legal studies emphasise that the growing phenomenon of market competition may lead to the creation of a monopoly, which constitutes one of the practices contrary to free competition, through the exploitation of a dominant position by a particular undertaking, thereby causing harm to the remaining market participants. In this context, the State bears the responsibility of ensuring protection and safeguarding the various interests involved in a manner that ultimately guarantees the public interest. This falls within the concept of competitive public order, which can be realised only within a framework that ensures freedom while simultaneously setting limits to it. This approach is embodied in the provisions of competition law.